Harnessing Twitter to empower scientific engagement and communication: The ISTH 2020 virtual congress experience. Issue 2 (8th March 2021) - Othman, Maha; Cormier, Matthew; Barnes, Geoffrey D.; Comer, Shane P.; Connors, Jean M.; Denorme, Frederik; Khorana, Alok A.; Las Casas, Pedro Henrique; Morla, Shravan; Muia, Joshua; Ní Áinle, Fionnuala; Taylor, Kirk A.; et al.
Abstract: As a result of the coronavirus disease 2019 pandemic, the International Society on Thrombosis and Haemostasis (ISTH), like many societies around the world, canceled their in‐person hematology congress planned for Milan, Italy, in July 2020. As a result, the first virtual ISTH congress in the organisation's 51‐year history was delivered, inviting free registration from across the globe. As part of the social media support, marketing, and scientific dissemination efforts for the virtual congress, the ISTH assembled a group of official Twitter Ambassadors, which represented the broad and diverse ISTH community. Ambassadors were tasked to tweet daily throughout the congress and to share their commentary on the hematology research being presented with the "#ISTH2020" hashtag. Ambassadors were also supported by Twitter activities from the two official ISTH‐affiliated journals: the Journal of Thrombosis and Haemostasis ( JTH ) and Research and Practice in Thrombosis and Haemostasis ( RPTH ). In this forum and through the Twitter ambassadors' lens, we present the Twitter Ambassadors' experience, reflect on the impact of social media on the ISTH 2020 congress, and share this experience with the wider scientific community. Specifically, we report on the role of Twitter communication for virtual meetings, discuss the pros and cons of the virtual congress, and offer Twitter‐related recommendations for future virtual or blended congresses. We conclude that the ISTH Twitter Ambassador program broadened social media engagement and offers a novel route to improve social connectivity in the virtual research congress setting.